2013
DOI: 10.1118/1.4794496
|View full text |Cite
|
Sign up to set email alerts
|

Dose response of selected ion chambers in applied homogeneous transverse and longitudinal magnetic fields

Abstract: Care must be taken when making ion chamber measurements in a transverse magnetic field. Ion chamber responses vary not only with transverse field strength, but with chamber orientation and type, and can be considerable. Longitudinal magnetic fields influence ion chamber responses relatively little (2% at 1.5 T), and only at field strengths in excess of 1.0 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
145
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(156 citation statements)
references
References 32 publications
11
145
0
Order By: Relevance
“…Reynolds et al [11] found results similar to those of Meijsing et al and showed that the orientation of the B-field with respect to the chamber itself also has an effect. They also found that the response of ionization chambers was relatively stable for inline MR-linacs where the B-field is parallel to the beam.…”
Section: Ionization Chamber Responsesupporting
confidence: 79%
See 1 more Smart Citation
“…Reynolds et al [11] found results similar to those of Meijsing et al and showed that the orientation of the B-field with respect to the chamber itself also has an effect. They also found that the response of ionization chambers was relatively stable for inline MR-linacs where the B-field is parallel to the beam.…”
Section: Ionization Chamber Responsesupporting
confidence: 79%
“…As a result, there is great interest in developing new external-beam radiotherapy machines with integrated MRI [3][4][5][6][7]. However, since MRI requires magnetic (B) fields, the Lorentz force influences the trajectories of the secondary electrons, which in turn affects both the dose distribution in water [1,8,9] and the dose-response of ionization chambers [6,[10][11][12] and several other detectors [13,14]. Thus, dosimetry in the presence of a B-field requires understanding both the B-field effects on the dose distribution and the response of detectors.…”
Section: Introductionmentioning
confidence: 99%
“…An Elekta 6MV FFF linear accelerator beam model served as input for a 30x30x20 cm 3 water phantom in which the chamber was placed in 10cm depth.…”
Section: Methodsmentioning
confidence: 99%
“…First investigations into this topic have found that the response of a thimble type ionization chamber is highly dependent on the angle between the axis of the ionization chamber and the axis of the magnetic field [1][2][3][4]. Assuming that the axis of a thimble type chamber should be perpendicular to the incoming beam and the magnetic field axis is also perpendicular to the incoming beam, this angle α is the only degree of freedom left for a full description of the ionization chamber's orientation (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the main reasons for the development of these alternatives to the existing options include the increasing interest in combining a MRI scanner with a radiotherapy linear accelerator (linac), the development of heavy ion and particle beams in radiotherapy and the introduction of new small animal irradiation platforms for radiobiological investigations. These new technologies present different problems from the effect of magnetic fields on dosemeters, 18 the response of dosemeters in different types of treatment beams, 19,20 the miniaturization of treatment fields 21,22 and the associated complexity of radiation dosimetry at very small field sizes. 23,24 Optical fibres offer a solution for in vivo radiotherapy dosimetry with many advantages over currently employed clinical dosimetry systems.…”
mentioning
confidence: 99%